Inclusión de tres dosis de harina de gandul (Cajanus cajan (l). millsp) en el engorde de pollos broiler en el recinto el vergel, cantón Valencia. - Cajas Cusme, Darwin Adalberto (2015)
This research was conducted to assess the effects of including pigeon pea flour on growth indices of broiler chicken and establish the profitability of the treatments under study; It was held on the property of Mrs. Carmen Cusme located on the grounds Gonzalez Suarez in the Km 8 route to the Vergel of Valencia Canton in the Province of Los Ríos, whose geographical coordinates are 0 ° 57'09 '' to south latitude and 79 ° 21'11 '' west longitude, 60 meters, the investigation lasted 90 days. Treatments are more balanced supply of pigeon pea flour in the finishing phase and completion of pigeon pea flour T1 0%, 10% T2, T3 15% and T4 20% pigeon pea flour with 4 repetitions, the experimental unit was 6 chickens, Design Randomized Complete Blocks (DBCA) was applied for comparison of means test Tukey multiple range 95% probability was used. The results show that the higher feed intake 7100.38 g, 4413.50 g heavier, more weight gain response 4366.42g introduced the T1 0% pigeon pea flour. The greatest response feed conversion 1.63 introduced the T1 0% pigeon pea flour. Final weight excels treatment T1 (0% pigeon pea flour) with 4413.50 g, stands between treatments T2 treatment (10% pigeon pea flour) to 4215.50. Carcass weight to excel T1 (0% pigeon pea flour) to 3550.25. In percentage yield excel T2 (5% pigeon pea flour) treatment with 80.68%. The lower cost $ 38.14 USD per treatment has on the T1 (control) treatment. The higher income to $ 121.08, $ 82.94 more useful and better cost / benefit ratio of 3.17 recorded at T1 (control) treatment.